(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Strategic Management has become an essential nowadays as managerial techniques have been developed and used successfully by many of professional business corporation such as General electric and the Boston Consulting Group. Initially strategic Management was of most use to professional corporations operating in multiple industries. Increasing risk of error, costly mistakes, misunderstanding market needed and even economic ruin are causing todays professional managers in all organizations to take Strategic Management seriously in order to keep their companies competitive in an increasingly volatile environment. In this study we will focus on Suppliers who deal with sanitary ware (Bathroom accessories, Mixers, Bathtub) in Makkah and Jeddah Cities, Kingdom of Saudi Arabia. Mostly people in Makkah and Jeddah Cities prefer to purchase from various outlets vendors / retailers who are available usually in same area, according to their convenience, preference and selection. Increases in expectations and changing culinary style of consumers make the Sanitary Ware (Bathroom accessories, Mixers, Bathtub) business dynamic in general. Despite the increasing interest in the area there are very little researches on Superior Competitive Advantage of sanitary ware vending service in our domestic market. Keeping these conditions in view, this study tries to explore the current scenario in which Sanitary Ware (Bathroom accessories, Mixers, Bathtub) has become a flourishing business for a lot of Suppliers as it has been successful in attracting a large mass of customers and projects.This study analyses Strategic Management as the key for Superior Competitive Advantage of Sanitary Ware (Bathroom accessories, Mixers, Bathtub) in Makkah and Jeddah Cities. The present survey has been done with 112 retailers who purchase sanitary ware from sanitary ware suppliers companies in Makkah and Jeddah Cities. It identifies the most relevant understanding of StrategicManagement as the key for Superior Competitive Advantage, and determines their influence in choosing of Sanitary Ware outlets. The results show that Strategic Management as independent variable has a positive influence on Superior Competitive Advantage of Sanitary ware suppliers in Makkah and Jeddah Cities.